THE STUDENTS’ PREFERENCES OF ONLINE LEARNING DURING COVID-19 PANDEMIC - Andi Rahmi Utami; Muhammad Asfah Rahman; Maemuna Muhayyang (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This research aimed to find out the kind of online learning the students prefer and the reasons why the students prefer the online learning in learning English at SMA Negeri 16 Makassar. This research applied mixed methods research design. The data were collected from the questionnaire and interview. The subject of this study was the second-grade social science students. The questionnaire was conducted on 98 students and the interview was conducted on 12 students. The result of this research showed that the mean score of the students' preference in synchronous was (46,17) indicated "like" category and the mean score of the students' preference in asynchronous was (44,64) indicated "neutral" category. From the result, the researchers found that the mean score of synchronous was higher than asynchronous. The reasons why the students prefer synchronous are because there is the direct interaction between the students and teacher, being easy to understand, direct demonstration, and good emotional relationship between the students and teacher. Meanwhile, the students prefer asynchronous because there is saved task history, the materials can be repeated, providing clear materials, and facilitating assignment submission. Therefore, it can be concluded that the students prefer synchronous. Synchronous can be used to deliver the material and asynchronous can be used to provide the material or task, and students' assignment submission.